Improving serodiagnosis of human and canine leishmaniasis with recombinant Leishmania braziliensis cathepsin l-like protein and a synthetic peptide containing its linear B-cell epitope. - Daniel Menezes-Souza; Tiago Antônio de Oliveira Mendes; Matheus de Souza Gomes; Daniella Castanheira Bartholomeu; Ricardo Toshio Fujiwara (Public Library of Science (PLoS), 2015)
The early and correct diagnosis of human leishmaniasis is essential for disease treatment. Another important step in the control of visceral leishmaniasis is the identification of infected dogs, which are the main domestic reservoir of L. infantum. Recombinant proteins and synthetic peptides based on Leishmania genes have emerged as valuable targets for serodiagnosis due to their increased sensitivity, specificity and potential for standardization. Cathepsin L-like genes are surface antigens that are secreted by amastigotes and have little similarity to host proteins, factors that enable this protein as a good target for serodiagnosis of the leishmaniasis.We mapped a linear B-cell epitope within the Cathepsin L-like protein from L. braziliensis. A synthetic peptide containing the epitope and the recombinant protein was evaluated for serodiagnosis of human tegumentary and visceral leishmaniasis, as well as canine visceral leishmaniasis.The recombinant protein performed best for human tegumentary and canine visceral leishmaniasis, with 96.30% and 89.33% accuracy, respectively. The synthetic peptide was the best to discriminate human visceral leishmaniasis, with 97.14% specificity, 94.55% sensitivity and 96.00% accuracy. Comparison with T. cruzi-infected humans and dogs suggests that the identified epitope is specific to Leishmania parasites, which minimizes the likelihood of cross-reactions.